Perancangan Sistem Informasi E-Arsip Pada Laboratorium Kualitas Karet PT. Batanghari Tembesi - Febri Annisa; Dodi Sandra; Ronald Naibaho (LPPM STIKOM Dinamika Bangsa, 2024)
This research was conducted at the Rubber Quality Laboratory of PT. Batanghari Tembesi Jambi. Rubber Quality Laboratory PT. Batanghari Tembesi is a unit that functions to analyze the quality of rubber that has been processed. This research aims to create an E-Archive Information System to overcome archive management that occurs at the Rubber Quality Laboratory of PT. Batanghari Tembesi, where this company still uses paper for archiving, namely the data from the SIR analysis and the results of the Cross Check data are printed and then stored in cupboards and cardboard boxes, which can cause the data to be prone to loss, damage, and take a long time to search for the data. The waterfall model is used in developing this information system because the work flow is clearer and more sequential, so that the development process works more regularly and focused. Meanwhile, in designing this system, system modeling tools such as Use Case Diagrams, Class Diagrams, and Activy Diagrams were used.